A primer on pulsed power and linear transformer drivers for high energy density physics applications - McBride,RD; Stygar,WA; Cuneo,ME; Sinars,DB; Mazarakis,MG; Leckbee,JJ; Savage,ME; Hutsel,BT; Douglass,JD; Kiefer,ML; Oliver,BV; Laity,GR; et al. (IEEE Transactions on Plasma Science, 2018)
The objectives of this tutorial are as follows: 1) to help students and researchers develop a basic understanding of how pulsed-power systems are used to create high-energy-density (HED) matter; 2) to develop a basic understanding of a new, compact, and efficient pulsed-power technology called linear transformer drivers (LTDs); 3) to understand why LTDs are an attractive technology for driving HED physics (HEDP) experiments; 4) to contrast LTDs with the more traditional Marx-generator/pulse-forming-line approach to driving HEDP experiments; and 5) to briefly review the history of LTD technology as well as some of the LTD-driven HEDP research presently underway at universities and research laboratories across the globe. This invited tutorial is part of the Mini-Course on Charged Particle Beams and High-Powered Pulsed Sources, held in conjunction with the 44th International Conference on Plasma Science in May of 2017.